Nanoparticle-Reinforced Associative Network Hydrogels - Agrawal, Sarvesh K. (2008)
ABA triblock copolymers in solvents selective for the midblock are known to form associative micellar gels. We have modified the structure and rheology of ABA triblock copolymer gels comprising poly(lactide)-poly(ethylene oxide)-poly(lactide) (PLA-PEO-PLA) through addition of a clay nanoparticle, laponite. Addition of laponite particles resulted in additional junction points in the gel via adsorption of the PEO corona chains onto the clay surfaces. Rheological measurements showed that this strategy led to a significant enhancement of the gel elastic modulus with small amounts of nanoparticles. Further characterization using SAXS and DLS confirmed that nanoparticles increase the intermicellar attraction and result in aggregation of PLA-PEO-PLA micelles.